Polymer for preparing adhesive-free flexible copper-clad plate

By polymerizing polyimide oligomers with reactive unsaturated groups and polyphenylene ether oligomers in glue-free flexible copper clad material, the polyimide/polyphenylene ether block copolymer was solved The existing materials have poor dielectric performance and high water absorption in high-frequency and high-speed circuits, which have achieved performance that is more suitable for high-frequency and high-speed electrical signal transmission circuits of 5G and above.

CN119409913APending Publication Date: 2025-02-11DATONG CO POLYMER (XIAN) TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411679602.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing glueless flexible copper clad material has poor dielectric performance in high-frequency and high-speed circuits and has high water absorption rate, resulting in the performance in 5G and above high-frequency high-speed electrical signal transmission circuits that cannot meet the requirements.

Method used

Polyimide oligomers and polyphenylene ether oligomers with active unsaturated groups are polymerized under the action of initiators to form polyimide/polyphenylene ether block copolymers for the preparation of glueless flexibility Copper clad plate.

Benefits of technology

This material combines the mechanical properties and heat resistance of polyimide resin, as well as the low dielectric constant, low dielectric loss and low water absorption of polyphenylene ether resin, and is suitable for high-frequency and high-speed printed circuits with glue-free flexible covering Copper plate, especially high-frequency high-speed electrical signal transmission circuits of 5G and above.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005147969490000031
    Figure BDA0005147969490000031
  • Figure BDA0005147969490000032
    Figure BDA0005147969490000032
  • Figure BDA0005147969490000051
    Figure BDA0005147969490000051
Patent Text Reader

Abstract

The invention discloses a polymer for preparing an adhesive-free flexible copper-clad plate. The polymer is formed by polymerizing an active unsaturated group-terminated polyimide oligomer and an active unsaturated group-terminated polyphenyl ether oligomer under the action of an initiator, the polyimide / polyphenyl ether block copolymer, which is synthesized by taking unsaturated group-terminated small molecular weight polyimide and polyphenyl ether polymer as raw materials and adopting a free radical polymerization technology, not only has the characteristics of good mechanical property and heat resistance of polyimide resin, but also has the characteristics of dielectric property and low water absorption of polyphenyl ether resin; the adhesive-free flexible copper-clad plate base material overcomes the defect that polyimide resin is used as an adhesive-free flexible copper-clad plate base material, and is more suitable for high-frequency and high-speed printed circuit adhesive-free flexible copper-clad plate base materials, especially for 5G and above high-frequency and high-speed electric signal transmission circuit adhesive-free flexible copper-clad plate base materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electronic materials, and in particular relates to a polymer for preparing a non-adhesive flexible copper-clad laminate. Background Art

[0002] Flexible printed circuit boards (FPCBs) are light, thin, and flexible. In the early days, they were mainly used as flat cables for static connections of electronic devices such as computers and cameras. Later, they were used as hinge cables for dynamic connections of electronic devices such as laptops and mobile phones. They can also be used for three-dimensional wiring installation, which meets the development requirements of electronic devices to be light, thin, short, and small. In the past decade, the signal processing and transmission frequency of electronic devices has increased rapidly, from megahertz (MHz) to gigahertz (GHz), and signal transmission has become more high-frequency and high-speed, which puts forward requirements for electronic circuit substrates used for signal transmission to have high-frequency and high-speed characteristics. Flexible copper clad laminates (FCCLs) as FPC substrates are correspondingly required to have lower dielectric constants and lower dielectric loss tangents.

[0003] At the same time, 5G application scenarios place higher demands on the electrical performance and thermal linear stability of adhesive-free flexible copper clad laminates used to make high-frequency and high-speed flexible circuits, with dielectric constants Dk (10GHz) ≤ 3.4 and dielectric loss Df (10GHz) ≤ 0.005. While requiring low Dk and low Df, the substrate linear expansion coefficient (CTE) is also required to be as close to that of copper foil as possible, with the lowest possible water absorption and higher thermal performance. Therefore, many adhesive-free flexible copper clad laminates used as 5G high-frequency and high-speed flexible circuits cannot meet the requirements at the same time.

[0004] In order to solve the above problems, polyimide (PI) resin is used as the substrate of non-adhesive flexible copper clad laminate (FCCL). Although polyimide resin film has excellent mechanical properties and heat resistance, such as tensile strength of more than 400MPa, glass transition temperature of more than 450℃, and good signal stability at high and low temperatures. However, its dielectric properties in high-frequency and high-speed circuits are not satisfactory. For example, its dielectric constant is 3.5-4.0, and the dielectric loss is often greater than 0.01; the peel strength between it and the copper foil of the copper clad laminate material is less than 1N / mm. In addition, polyimide resin has a large hygroscopicity, generally reaching more than 2%. This disadvantage may lead to reduced reliability of FPC under high humidity conditions, including oxidation of copper foil and reduced peel strength caused by evaporation of water vapor at high temperature. At the same time, the curling phenomenon caused by polyimide film after absorbing moisture will cause troubles in use. Therefore, polyimide resin is not an ideal material for preparing high-frequency and high-speed circuits.

[0005] In order to find better materials for the preparation of high-frequency and high-speed communication circuits for 5G and above, researchers have turned their attention to thermoplastic high molecular weight polymers such as polyphenylene ether (PPO or PPE). The structure of polyphenylene ether is symmetrical, and contains a large number of rigid benzene ring structures, and has more side methyl groups, rigid molecular chains, and no strong polar groups. These structural characteristics give PPO resin a low dielectric constant and low dielectric loss. In the temperature range of -150°C to 200°C and the frequency range of 10Hz to 10GHz, the dielectric constant (Dk, 2.4~2.5) and dielectric loss (Df, about 0.0007) are low and not affected by temperature and frequency changes. Its water absorption rate is not more than 0.05%. These excellent properties have laid the foundation for it as an electronic material, and it is very suitable for the preparation of high-frequency electronic communication substrates. However, the glass transition temperature of PPO resin at 210°C is relatively low, the heat resistance is poor, and the process adaptability is poor, which affects its application in the flexible copper clad laminate industry. Summary of the invention

[0006] The purpose of the present invention is to provide a polymer for preparing an adhesive-free flexible copper-clad laminate, so as to solve the problem that the dielectric constant, dielectric loss and other properties of the polymer for preparing an adhesive-free flexible copper-clad laminate cannot meet the requirements.

[0007] The present invention adopts the following technical scheme: a polymer for preparing a non-adhesive flexible copper-clad laminate, the polymer is polymerized by active unsaturated group-terminated polyimide oligomer and active unsaturated group-terminated polyphenylene ether oligomer under the action of an initiator.

[0008] Furthermore, the structural formula of the active unsaturated group-terminated polyimide oligomer is:

[0009]

[0010] in,

[0011] R1 is a benzene ring group, a phenyl group, a biphenyl group, a diphenyl ether group, a diphenylmethane group, a diphenyl ketone group, a diphenyl sulfone group, anthracene group or naphthyl group;

[0012] R2 is phenyl, biphenyl, diphenyl ether, diphenylmethane, benzophenone, diphenyl sulfone, bisphenoxybiphenyl, bisphenoxyphenyl, 2-(4-phenyl)-5-benzimidazolyl, 2-(4-phenyl)-5-benzoxazole, 4,4-bis(3-phenoxy)diphenylsulfone, anthracenyl or naphthyl;

[0013] R3 is 4-phenylethynylphthalimide, maleimide, acrylimide, methacrylimide or 4-vinylbenzimide.

[0014] Furthermore, the structural formula of the active unsaturated group-terminated polyphenylene ether oligomer is:

[0015]

[0016] Wherein, R is acryloyl, methacryloyl or 4-vinylbenzoyl.

[0017] Furthermore, the average molecular weight of the polyimide oligomer terminated with active unsaturated groups is 1000-1500.

[0018] Furthermore, the average molecular weight of the polyphenylene ether oligomer terminated with active unsaturated groups is 1500-3000.

[0019] Furthermore, the initiator is an azo compound, a peroxide, a peroxycarboxylic acid ester or a ketone peroxide.

[0020] Furthermore, the molar ratio of the polyimide oligomer terminated with an active unsaturated group to the polyphenylene ether oligomer terminated with an active unsaturated group is 1:1.

[0021] Furthermore, the amount of the initiator used is 1% to 20% of the sum of the molar numbers of the polyimide oligomer terminated with an active unsaturated group and the polyphenylene ether oligomer terminated with an active unsaturated group.

[0022] Furthermore, the amount of the initiator used is 10% of the sum of the molar numbers of the polyimide oligomer terminated with an active unsaturated group and the polyphenylene ether oligomer terminated with an active unsaturated group.

[0023] The beneficial effects of the present invention are:

[0024] The present invention uses unsaturated group-terminated low molecular weight polyimide and polyphenylene ether polymer as raw materials and adopts free radical polymerization technology to synthesize the polyimide / polyphenylene ether block copolymer, which has the characteristics of good mechanical properties and heat resistance of polyimide resin, and the characteristics of dielectric properties and low water absorption of polyphenylene ether resin, overcomes the disadvantages of polyimide resin used as adhesive-free flexible copper clad laminate substrate, and is more suitable for adhesive-free flexible copper clad laminate substrate of high-frequency and high-speed printed circuit, especially for adhesive-free flexible copper clad laminate substrate of 5G and above high-frequency and high-speed electrical signal transmission circuit;

[0025] The polyphenylene ether resin of the present invention is cheaper than polyimide resin, so the price of the prepared polyimide / polyphenylene ether block copolymer is lower than that of the polyimide resin substrate, which can improve the performance of the adhesive-free flexible copper clad laminate while reducing its cost and improving its market competitiveness. DETAILED DESCRIPTION

[0026] The present invention is described in detail below in conjunction with specific implementation modes.

[0027] The invention discloses a polymer for preparing a non-adhesive flexible copper-clad laminate. The polymer is prepared by polymerizing a polyimide oligomer terminated by an active unsaturated group and a polyphenylene ether oligomer terminated by an active unsaturated group under the action of an initiator.

[0028] Wherein, the structural formula of the polyimide oligomer terminated with active unsaturated groups is:

[0029]

[0030] in,

[0031] R1 is a benzene ring group, a phenyl group, a biphenyl group, a diphenyl ether group, a diphenylmethane group, a diphenyl ketone group, a diphenyl sulfone group, anthracene group or naphthyl group;

[0032] R2 is phenyl, biphenyl, diphenyl ether, diphenylmethane, benzophenone, diphenyl sulfone, bisphenoxybiphenyl, bisphenoxyphenyl, 2-(4-phenyl)-5-benzimidazolyl, 2-(4-phenyl)-5-benzoxazole, 4,4-bis(3-phenoxy)diphenylsulfone, anthracenyl or naphthyl;

[0033] R3 is 4-phenylethynylphthalimide, maleimide, acrylimide, methacrylimide or 4-vinylbenzimide.

[0034] Wherein, the structural formula of the active unsaturated group-terminated polyphenylene ether oligomer is:

[0035]

[0036] Wherein, R is acryloyl, methacryloyl or 4-vinylbenzoyl.

[0037] More specifically, the average molecular weight of the polyimide oligomer terminated with an active unsaturated group is 1000 to 1500. The average molecular weight of the polyphenylene ether oligomer terminated with an active unsaturated group is 1500 to 3000.

[0038] More specifically, the initiator is an azo compound, a peroxide, a peroxycarboxylic acid ester or a ketone peroxide. The amount of the initiator is 1% to 20% of the total molar number of the polyimide oligomer terminated with an active unsaturated group and the polyphenylene ether oligomer terminated with an active unsaturated group. Preferably, the amount of the initiator is 10% of the total molar number of the polyimide oligomer terminated with an active unsaturated group and the polyphenylene ether oligomer terminated with an active unsaturated group.

[0039] More specifically, the molar ratio of the polyimide oligomer terminated with an active unsaturated group to the polyphenylene ether oligomer terminated with an active unsaturated group is 1:1.

[0040] Example 1

[0041] Preparation of polyimide / polyphenylene ether block copolymers:

[0042] Step 1: High-purity argon gas was introduced into a 250 ml three-necked round-bottom flask with a condenser. After 30 minutes, 50% of the total mass of N,N-dimethylacetamide and 0.01 mol of 4-phenylethynylphthalimide-terminated polyimide oligomer were added into the round-bottom flask.

[0043] Among them, the code name of the polyimide oligomer terminated with 4-phenylethynylphthalimide is a.

[0044] Step 2: Start stirring at a speed of 20 to 30 rpm, and add 0.01 mol of 4-vinylbenzoyl-terminated polyphenylene ether oligomer; wherein the code of 4-vinylbenzoyl-terminated polyphenylene ether oligomer is x.

[0045] Step 3: Add the remaining 50% of N,N-dimethylacetamide. At this point, the solid content of the material in the round-bottom flask is 20%.

[0046] Step 4: After stirring at 25°C for 0.5h, the temperature was raised to 80°C and reacted for 7h. When the viscosity was 30000-40000mPa·S, the temperature was lowered to below 30°C to obtain a polymer glue having a solid content of 30%.

[0047] In a Class 10,000 clean environment, the polymer adhesive was coated on a clean and intact glass plate with a size of 150 mm x 200 mm x 5 mm by a coater; the glass plate coated with the polymer adhesive was placed in an explosion-proof oven for curing to obtain a polymer film with a thickness of 25 μm; wherein the curing process conditions were: 80℃ / 5min→120℃ / 5min→150℃ / 5min→180℃ / 5min→200℃ / 5min.

[0048] Other parameters not mentioned in this example are shown in Table 1. The performance test results of the prepared polymer film are shown in Table 2.

[0049] The specific steps of Examples 2 to 16 are the same as those of Example 1, except for the types of the added active unsaturated group-terminated polyphenylene ether oligomers and active unsaturated group-terminated polyimide oligomers, as shown in Table 1.

[0050] Table 1 Types and amounts of raw materials used in Examples 1 to 16

[0051]

[0052] The meanings of the codes in Table 1 are:

[0053] a is a 4-phenylethynylphthalimide-terminated polyimide oligomer having an average molecular weight of 1000;

[0054]

[0055] b is a 4-phenylethynylphthalimide-terminated polyimide oligomer having an average molecular weight of 1500;

[0056]

[0057] c is a 4-vinylbenzamide-terminated polyimide oligomer having an average molecular weight of 1000;

[0058]

[0059] d is a 4-vinylbenzamide-terminated polyimide oligomer having an average molecular weight of 1500;

[0060]

[0061] e is a 4-phenylethynylphthalimide-terminated polyimide oligomer having an average molecular weight of 1000;

[0062]

[0063] f is a 4-phenylethynylphthalimide-terminated polyimide oligomer having an average molecular weight of 1500;

[0064]

[0065] g is a 4-vinylbenzamide-terminated polyimide oligomer having an average molecular weight of 1000;

[0066]

[0067] h is a 4-vinylbenzamide-terminated polyimide oligomer having an average molecular weight of 1500;

[0068]

[0069] x is a 4-vinylbenzoyl-terminated polyphenylene ether oligomer having an average molecular weight of 1500;

[0070]

[0071] y is a 4-vinylbenzoyl-terminated polyphenylene ether oligomer having an average molecular weight of 3000;

[0072]

[0073] Wherein, the initiator is azobisisobutyronitrile and the solvent is N,N-dimethylacetamide.

[0074] The performance of the polymer films prepared in Examples 1 to 16 was tested. The results are shown in Table 2, wherein the dielectric properties were tested according to the methods specified in JPCA-DG03 and JPCA-M002 (E72), the peel strength was tested according to the method specified in IPC-TM-650 2.4.8.1; the water absorption was tested according to the method specified in GB / T1034-2023, and the test conditions were: 23°C, 50% humidity, 24h; T g Follow the method specified in B / T37631-2021.

[0075] Table 2 Performance data of polymer films prepared in Examples 1 to 16

[0076]

[0077]

[0078] Note: g It is the glass transition temperature of the film. The higher the value, the better the heat resistance of the tested sample.

[0079] As can be seen from Table 2, the maximum dielectric constant of the polymer films prepared in Examples 1 to 16 is 3.34 and the minimum is 2.53, the maximum dielectric loss Df is 0.0040 and the minimum is 0.0015, indicating that the dielectric properties are excellent, the minimum peel strength is 1.06 and the maximum is 1.65, indicating that the mechanical properties are good; the maximum water absorption is 0.65 and the minimum is 0.31, indicating that the environmental adaptability is good. g The lowest temperature is 302℃ and the highest temperature is 361℃, which shows that it has good heat resistance.

[0080] In summary, the comprehensive performance of the polyimide / polyphenylene ether block copolymer prepared by the present invention is better than the corresponding performance of the adhesive-free flexible copper clad laminate substrate polyimide and polyphenylene ether in the background technology. It can be used as an adhesive-free flexible copper clad laminate substrate to improve its performance and increase application scenarios, and can be used as an adhesive-free flexible copper clad laminate substrate for 5G and above electronic circuits.

[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A polymer for preparing a non-adhesive flexible copper-clad laminate, characterized in that: The polymer is prepared by polymerizing a polyimide oligomer terminated by an active unsaturated group and a polyphenylene ether oligomer terminated by an active unsaturated group under the action of an initiator.

2. A polymer for preparing a non-adhesive flexible copper-clad laminate according to claim 1, characterized in that: The structural formula of the active unsaturated group-terminated polyimide oligomer is: in, R1 is a benzene ring group, a phenyl group, a biphenyl group, a diphenyl ether group, a diphenylmethane group, a diphenyl ketone group, a diphenyl sulfone group, anthracene group or naphthyl group; R2 is phenyl, biphenyl, diphenyl ether, diphenylmethane, benzophenone, diphenyl sulfone, bisphenoxybiphenyl, bisphenoxyphenyl, 2-(4-phenyl)-5-benzimidazolyl, 2-(4-phenyl)-5-benzoxazole, 4,4-bis(3-phenoxy)diphenylsulfone, anthracenyl or naphthyl; R3 is 4-phenylethynylphthalimide, maleimide, acrylimide, methacrylimide or 4-vinylbenzimide.

3. The polymer for preparing a non-adhesive flexible copper-clad laminate according to claim 1, characterized in that: The structural formula of the active unsaturated group-terminated polyphenylene ether oligomer is: Wherein, R is acryloyl, methacryloyl or 4-vinylbenzoyl.

4. The polymer for preparing a non-adhesive flexible copper-clad laminate according to claim 1, characterized in that: The average molecular weight of the active unsaturated group-terminated polyimide oligomer is 1000-1500.

5. The polymer for preparing a non-adhesive flexible copper clad laminate according to claim 1, characterized in that: The average molecular weight of the active unsaturated group-terminated polyphenylene ether oligomer is 1500-3000.

6. The polymer for preparing a non-adhesive flexible copper-clad laminate according to claim 1, characterized in that: The initiator is an azo compound, a peroxide, a peroxycarboxylic acid ester or a ketone peroxide.

7. The polymer for preparing a non-adhesive flexible copper clad laminate according to claim 1, characterized in that: The molar ratio of the active unsaturated group-terminated polyimide oligomer to the active unsaturated group-terminated polyphenylene ether oligomer is 1:

1.

8. The polymer for preparing a non-adhesive flexible copper clad laminate according to claim 1, characterized in that: The amount of the initiator used is 1% to 20% of the sum of the molar numbers of the polyimide oligomer terminated with active unsaturated groups and the polyphenylene ether oligomer terminated with active unsaturated groups.

9. The polymer for preparing a non-adhesive flexible copper-clad laminate according to claim 8, characterized in that: The amount of the initiator used is 10% of the sum of the molar numbers of the polyimide oligomer terminated with active unsaturated groups and the polyphenylene ether oligomer terminated with active unsaturated groups.